Penerapan Anggaran Produksi Dalam Upaya Pengendalian Biaya Produksi Untuk Meningkatkan Laba Pada Pia Latief Kediri - Eky Irdia Esta Narhensa; Khasanah Sahara; Beby Hilda Agustin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The application of the production budget is important for the company because used as a control tool. The production budget is the basis for making a production cost budget which is determined based on plans and sales. The purpose of this research was carried out based on the preparation of the production budget, to determine the level of production needed in Pia Latief Kediri Household Industry. The type of research used is descriptive quantitative, which provides an overview of the actual state of the object under study based on facts, by collecting and processing related data, namely raw material costs, labor costs, and factory overhead costs. The data studied is in 2020 to 2021 as the basis for calculating sales forecasts in 2022. From the results of the research, it shows that the application of the production budget is more controlled than before, because there is a difference between the budget that has been prepared and its realization, which results in a difference in profit and loss of IDR 10,420,000. So with these results it is suggested to Pia Latief Kediri Home Industry to prepare a production budget for the company to get a bigger profit than the previous year. Keywords: Production Budget, Production Cost Control, Profit.